Management of idiopathic granulomatous mastitis: dilema in diagnosis and management (Journal of Surgical Sciences, 2020)
Background: Idiopathic granulomatous mastitis is a rare disease of the breast. Clinically and radiologically it may mimic breast carcinoma. To date, there is no agreed gold standard treatment for IGM. The clinical management often starts with tests to eliminate microbial infection and when microbial infection can be ruled out, long-term oral steroid treatment or surgery is administered.Objective: To see the response of different treatment options of idiopathic granulomatous mastitis.Methods: This is a retrospective study involved 50 patients who were diagnosed with IGM and were treated in our institution between January 2009 to December 2016.Results: The mean age of patients was 34.3 years. Breast lump was the most common presentation. The right breast was affected in 30 cases & left breast 20 cases. 4 patients were pregnant at the time of presentation. Lactation within 6 months of presentation was documented in 4patients.45 patients used contraceptives pills. A clinical suspicion of malignancy was present in 17 cases. Mammography was performed in 20 patients and showed focal asymmetrical dense lesions in 9, well-circumscribed opacity in 8, speculated lesion in 1, and was normal in 2. Fine-needle aspiration was performed in 40 patients. Wide local excision was the mainstay of treatment. One patient underwent mastectomy due to recurrence and the final histology confirmed idiopathic granulomatous mastitis with no evidence of malignancy. 12 patients developed recurrence after a mean follow-up of 31.2 months.Conclusion: IGM is not so rare disease in our country. Clinical, radiologic, and even cytological findings are sometimes confused with malignancy. Adequate Surgical treatment as well as adjuvant therapeutic treatment are necessary. Knowledge, awareness and co-operation among surgeons and pathologist should also be strengthen to avoid unnecessary misdiagnosis and treatment.Journal of Surgical Sciences (2017) Vol. 21 (2): 89-93